BAPONGKA, SISTEM BUDAYA SUKU BAJO DALAM MENJAGA KELESTARIAN SUMBER DAYA PESISIR - Artanto, Yohanes Kristiawan (Sabda: Jurnal Kajian Kebudayaan, 2017)
Bajo communities have local knowledge which contains the value of the preservation of marine and coastal ecosystems in the form of traditions, rules or restrictions hereditarily practiced, maintained and adhered Bajo community in protecting and utilizing coastal areas sustainably. One is the activity called Bapongka (babangi), that is, the Bajo fishing activities conducted in groups for several weeks or even months using large sized boats called leppa or sopek. Bapongka has common values that can be interpreted as an attempt to tighten silaturrahmi (brotherhood relationship) among family members, as the activities are generally carried out by involving the family (wife and children) and also fellow fishermen, implemented by way of a group to use 3 to 4 boats set off hand in hand. The Bajo tribe's tradition is an activity that serves to safeguard the environment, preserve the resources, and prevent damage to marine and coastal ecosystems